Consequences of Splenectomy in Pancreatic Surgery: Should We Really Plan a Prophylactic Strategy for Splenectomized Patients? - Gallucci, Fernando; Uomo, Generoso (JOP. Journal of the Pancreas, 2012)
No abstract available. Image: Duodenum, pancreas and spleen model.